Exploring the Relationships between Social Competence, Academic Stress and Academic Performance among Undergraduate Students - Farheen Malik; Dr. Syeda Zunaira Fatima; Dr. Uzma Shahzadi (Research Journal of Psychology, 2025)
This study aimed to explored the relationships of social competence, academic stress and academic performance among undergraduate students. A quantitative research approach was adopted using a survey research design. The population comprised undergraduate students from public and private general universities in Punjab. A total of 866 students were selected through a multistage sampling technique from nine universities. Data were collected using two adapted instruments: the Multidimensional Social Competence Scale and the Student Stress Inventory Scale. The data were analyzed using descriptive statistics (mean, standard deviation, range) and correlation analysis. Findings revealed that students generally exhibited moderate levels of social competence and academic stress, while academic performance levels were relatively high. Social competence showed positively correlated with both academic stress and academic performance .Academic stress showed negatively correlated with academic performance. Based on these findings, it is recommended that universities implement structured social competence training programs and peer mentoring initiatives and provide academic counselling services to help students manage stress. These measures will foster a more supportive academic environment and enhance student success. This study offered a valuable insights for educator, policymakers, counselors, highlighted the need to enhance student social competences, reduce academic stress and improve overall academic performance.